A Regime Shift Toward a More Anoxic Environment in a Eutrophic Sea in Northern Europe - Almroth-Rosell, Elin; Wåhlström, Iréne; Hansson, Martin; Väli, Germo; Eilola, Kari; Andersson, Pia; Viktorsson, Lena; Hieronymus, Magnus; Arneborg, Lars (Frontiers in Marine Science, 2021)
Dissolved oxygen in the sea is essential for marine fauna and biogeochemical processes. Decline in the sea water oxygen concentration is considered to be an effect of eutrophication, also exacerbated by climate change. The Baltic Sea is one of the most eutrophic seas in the world and is located in northern Europe. It is a vulnerable, brackish, semi-enclosed sea, suffering from high pressures from human activity. This leads to increased hypoxic and anoxic areas, which can be used as a measure of the environmental state. In the present study the extent of anoxic (O2 < 0 ml l–1) and hypoxic (O2 < 2 ml l–1) areas were estimated for the autumns in 1960–2019 using vertical profiles of observed oxygen concentrations in the Baltic proper and four sub-areas of the Baltic proper: the Bornholm Basin, the western, northern and eastern Gotland basins. From vertical profiles of observed salinity, the annual average of the halocline depths in the four sub-basins were estimated. The results imply regime shifts toward increased anoxic area extents in the Gotland basins around the turn of the 20th century. In autumn 2018, the extent of anoxic bottom areas in the Baltic Sea was record high since the start of the data series. During the later part of the studied period the depths of the halocline coincide with the depth of the hypoxia in the Gotland basins. This implies that in these basins a worst-case scenario for the extent of hypoxic areas seems to be reached.